A methodology for the preliminary design and performance prediction of high-pressure ratio radial-inflow turbines. (1st December 2018) - Meroni, Andrea; Robertson, Miles; Martinez-Botas, Ricardo; Haglind, Fredrik
Abstract: Modern power generation technologies, such as organic Rankine cycle power systems, require turboexpanders operating with high-efficiency and high power density. These features often lead to high-pressure ratios machines, characterised by the presence of choking and supersonic flow conditions. This paper proposes a comprehensive methodology for the preliminary design and performance prediction of radial-inflow turbines operating at high-pressure ratios. A steady-state, mean-line model of a radial-inflow turbine is developed including real-gas effects and a detailed modelling strategy for the treatment of choking flow conditions. In addition, a set of loss models tailored to high-pressure ratio radial-inflow turbines is developed. After a global sensitivity analysis, the model is calibrated by means of a multi-objective optimisation with a Genetic Algorithm and using the data of six high-pressure ratio turbines with total-to-total pressure ratios up to 5.8. The calibration method allows a significant reduction in the overall predicted deviation of the turbine isentropic efficiency and mass flow rate. The design model yields predicted deviations in isentropic efficiency within ± 3 %-points and the off-design model within 5%. The methodology and the results are intended to be used as a benchmark for the future development of radial-inflow turbines in high-pressure ratio applications. Highlights: A mean-line model for high-pressure ratio radial-inflow turbines is presented. Modelling strategies for the treatment of choking conditions are detailed. The loss models are calibrated with the experimental data of six turbines. The calibration allowed reducing the deviation with the experimental data. The mean-line model is validated with other two test cases within 5% accuracy.